Prevalencia de Sarcocystis SP. en humanos en el área urbana de pasto Nariño - Astaiza Martínez, Juan Manuel; Castro Jay, Lucia Inés; Tumal Oviedo, Erika Susana; Hidalgo Troya, Arsenio (Universidad y Salud, 2006)
This study descriptive cross sectional was made in the urban area of the Pasto city, to determinate the prevalence of sarcocystis in the human being of this place using the ELISA Test in blood and the direct inmunofluresence Test (DIF) for zoites on feces. In the developed of this research a sampling of 95 people was used. The data capture was made by using a poll with clinical and environmental data which allowed the descriptive satatic and using a logistic regression model in the STAT GRAPHICS program. The samples were processed in the Colombian fundation for the parasite studies (FUNCEP) obtaining as result a prevalence of 78.94% and 100% in the ELISA and DIF Test. Considering the sociopolitical division of th city, the highest prevalence with test of ELISA was obtained in communes 2 and 12 (100%) and lowest it was obtained in commune 11.